Evaluation of Bomber Jackets Using Shaho Batik A Cultural Identity of Balikpapan East Kalimantan - Marthina Claudia Margaretha Sitohang; Eneng Lutfia Zahra; Rahayu Purnama (Universitas Negeri Surabaya, 2025)
This study aims to produce a bomber jacket using Shaho batik and to evaluate the aesthetic aspects of the bomber jacket made with Shaho batik from Balikpapan, East Kalimantan. This research employs a quantitative descriptive method with a pre-experimental research design in the form of a one-shot case study. As a result, five bomber jacket products were created using Shaho Batik and evaluated using a rating scale. The assessment instrument consisted of a questionnaire with 14 statements, measured using a rating scale, and was distributed to five expert panelists in the field. The aesthetic evaluation referred to three aspects: form or appearance, content or substance, and presentation or performance. Overall, the aesthetic evaluation achieved a score of 83.8%, classified as very good.